Influence of precipitate and grain sizes on the brittle-to-ductile transition in Fe–Al–V bcc-L21 ferritic superalloys - Ferreirós, Pedro Antonio (2022)
The limiting factors to achieving a wide application of bcc-superalloys are the high brittle-to-ductile transition temperatures (BDTT). The understanding of the mechanisms controlling the BDTT and how to optimise the microstructure in polycrystalline bcc-superalloys remains a concern today. In the present work, the influence of grain and coherent precipitates sizes on strength and brittle-to-ductile transition temperature (BDTT) are studied in a Fe78Al10V12 (A2+L21) ferritic superalloy, toward application in high-efficiency power plants. Additionally, the A2 matrix behaviour was evaluated in a derived single-phase-bcc Fe84Al8V8 alloy. Thermal ageing and coarsening treatments were applied to produce samples with different precipitate and grain sizes. Tensile tests were carried out at different temperatures and strain rates to assess the variation of the yield stress. Charpy impact tests were used to measure the BDTT in both alloys, which was substantially reduced with grain size refinement, and precipitate coarsening. It was found that the increase in cleavage stress by precipitation strengthening follows the same behaviour that the increase in yield stress for coherent strengthened bcc-superalloys. Integration into a physical-based model, which identified a novel interplay with cleavage stress, provides enhanced BDTT predictive capability for ferritic superalloys.